Effect of different bulking agents on the quality, microbial community structure and metabolic functions during human feces composting in foam composting device - Ning, Tianyang; Zheng, Xiangqun; Liang, Jiayin; Wang, Weihan; Zhang, Guowei; Wei, Xiaocheng; Tan, Lu (Frontiers in Microbiology, 2025)
Aerobic composting represents an efficacious strategy for the disposal of human feces, yet investigations into the effects of different bulking agents on this process remain limited. This study investigated the effects of composting human feces with four types of bulking agents—wheat straw, corn straw, millet straw, and sawdust—in a foam composting device, as well as the impacts of the process on the microbial community structure and metabolic functions adopting sequencing data analysis and metagenomic analysis. The results demonstrate that aerobic composting can safely treat human feces, resulting in a mature compost product. Comparative assessments of compost quality and microbial profiles with various bulking agents indicated superior performance of corn straw compost, surpassing those produced with wheat straw, millet straw, and sawdust in terms of humification level (HA/FA = 2.9), peak temperature reached (71.2°C), composting duration (20 days), and nutrient composition (TN 42.87 g/kg). Additionally, the diversity and dominance of certain microbial colonies (Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidota) were significantly higher in composts formulated with corn straw. The metagenomic data analysis reveals significant differences in the abundance of “carbon metabolism” and “microbial metabolism” among different groups, further indicating that the addition of different bulking agents affects the utilization of metabolic products, amino acids, and carbohydrates as carbon sources by microbes in human feces compost. Consequently, leveraging corn straw as a bulking agent, given its abundant availability, could potentially improve the efficiency and outcome of the human feces composting process.